Information needs and information-seeking behavior of University of the Philippines Diliman undergraduate students regarding their mental health during and after the Covid-19 pandemic - Estepa, Mark Lester C.; Dar Juan, Elijah John F. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2024)
The COVID-19 lockdown in the Philippines significantly impacted the lives of students, leading to an abrupt shift to remote learning starting in the Academic Year 2020-2021. causing mental health concern. This study delves into the mental health information needs and information-seeking behavior of University of the Philippines Diliman undergraduate students amidst and after the COVID-19 pandemic. Employing a qualitative exploratory design, the research aims to comprehend students’ reasons for seeking mental health information, their diverse information needs and sources, and the barriers and behaviors they encountered in seeking and utilizing such information. Data were gathered through in –depth interviews with nine respondents from the university’s academic clusters. These data were analyzed using thematic analysis and a code book. The finding reveals the students’ experiences during and after the pandemic influenced their motivations to seek mental health information, including the need for autonomy, relatedness, and competence, as well as other motivations, such as curiosity and interest in mental health. These shaped their various information needs and seeking behaviors. Recommendations include prioritizing mental health care resources and support systems and swift crisis response mechanism from both university and government institutions.
Thesis
Keywords: University of the Philippines (Diliman).; Information behavior; COVID-19 Pandemic, 2020-2023 -- Case studies; Mental health -- Case studies